The Role of Agricultural Instructors on the Income of Rejeki Alami Women Farmer Group Members - Alfitri, Sintia Gina; Dalmiyatun, Tutik; Mulyatno Setiawan, Bambang (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Agricultural extension is an activity carried out by agricultural instructors to improve skills, knowledge, and attitudes of farmers. Increasing the farmers’ knowledge may help to increase farm income and meet the family needs. This study aims to analyze the role of agricultural instructors, the income received by members of Rejeki Alami Women Farmer Group members, and the influence of the agricultural instructors’ role on the income of Rejeki Alami Women Farmer Group members. The research was conducted in Jimbaran Village, Kayen District, Pati Regency. Census sampling method was used by taking 30 members of Rejeki Alami Women Farmer Group. Data collection was carried out by commissioning, interview, and observation. Data were analyzed with descriptive analysis, income analysis, and multiple linear regression analysis. The results showed that the overall role of agricultural instructors on the group was fairly good with the percentage of 73.3%. The role of agricultural instructors as innovators, organizers, consultants, communicators, facilitators, and motivators is fairly good with the respective percentage values being 80%, 73.3%, 63.3%, 83.3%, 70% and 66.6%. The average income of the group members is IDR 260,326 per month in individual business, while their income in running group business is IDR 30,097. This shows that each member earns the same income in group business. Based on these results, it can be concluded that the role of agricultural instructors gives influence on the income of Rejeki Alami Women Farmer Group members.